Analysis of Affecting Factors to Patient Safety Incident at Mitra Medika Amplas Hospital - Novitalia, Anak Agung Sagung Dewi; Fitriani, Arifah Devi; Syafitri, Ramadhani (Journal La Medihealtico, 2024)
The study aimed to analyze factors that influence incident safety patients at Amplas Mitra Medika Hospital. Study This nature quantitative and use design cross sectional. Research done with give questionnaire to 72 nurses the executor taken with technique p roportionate stratified random sampling from a total population of 258 nurses. The data collection method used primary and secondary data which were analyzed using regression test logistics. Research result show that culture (p-value 0.008 < 0.05), condition work (p-value 0.002 < 0.05), and action No safe (p-value 0.007) < 0.05) has an effect significant to incident, while supervision (p-value 0.999) > 0.05) no influential to incident in a way partial. Analysis multivariate show There is influence significant from condition work and action No safe to incident in a way simultaneous with influence as big as 33.2%. The most dominant factor influential in the regression model is action No safe. Research conclusion This is factor culture, conditions work, and action No safe influential to incident, while factor supervision No influential. Research results expected can become considerations and input for House Sick For more optimize condition supportive work quality performance nurse, lower action No safe in giving care nursing to patient through improvement training, and developing culture safety patient through ambassador culture in effort prevent incidents and increase safety patient at home Sick.